Sinkronisasi UUPA Terhadap Peraturan Perundang-Undangan di Bidang Penetapan dan Penggunaan Hak Atas Tanah - Tuharea, Farida; Sari, Liani; Kurnia Katjong, Revie; Irsan, Irsan; Tuhumury, Harry A.; Nurlia Mamonto, Andi Annisa (LPPM Universitas Ekasakti Padang, 2024)
In achieving what is emphasized in article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia, it is neither necessary nor appropriate for the Indonesian people or the State to act as land owners, it is more appropriate if the State, as the power organization of the entire people (nation) acts as the Body. Ruler. It is from this angle that we must look at the meaning of the provisions in article 2 paragraph 1 of the UUPA which states that